2013
DOI: 10.1007/s00299-013-1448-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MV-generated ROS responsive EST clones in floral buds of Litchi chinensis Sonn.

Abstract: A suppression subtractive hybridization library was constructed using inflorescence primordia of 'Nuomici' litchi to identify EST clones responsive to MV-generated ROS. 93 ESTs could be aligned as unique gene sequences in the inflorescence primordia of litchi. Litchi is an evergreen woody tree widely cultivated in subtropical and tropical regions. However, defective flowering is a pending problem of litchi production. Our previous study indicated that reactive oxygen species (ROS) induced by methyl viologen di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…To investigate the expression of candidate NO responsive unique genes during normal floral tissue differentiation, we determined their relative expression in buds of the terminal shoots at the induction stage (25 December 2011), floral initiation stage (13 January 2012), rhachis developmental stages when apical and lateral axillary panicle began to develop (1, 5, and 12 February 2012), and floral organ developmental stage (20 February 2012) as described by Liu et al (2013). The results show that the relative expression of LcANR at the floral induction stage was low and increased by 121.0 and 162.6 % at the floral initiation stage and the early rhachis developmental stage, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the expression of candidate NO responsive unique genes during normal floral tissue differentiation, we determined their relative expression in buds of the terminal shoots at the induction stage (25 December 2011), floral initiation stage (13 January 2012), rhachis developmental stages when apical and lateral axillary panicle began to develop (1, 5, and 12 February 2012), and floral organ developmental stage (20 February 2012) as described by Liu et al (2013). The results show that the relative expression of LcANR at the floral induction stage was low and increased by 121.0 and 162.6 % at the floral initiation stage and the early rhachis developmental stage, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We isolated total RNA from floral buds or panicle primordia, and it was used to generate the first-strand cDNA according to the method of Liu et al (2013). The expression analysis was performed at the transcript level which was determined by RT-qPCR using single-stranded cDNA as template.…”
Section: Analysis Of Gene Expression By Rt-qpcrmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that reactive oxygen species (ROS) promoted flowering and decreased the chilling requirement for flowering [9] and obtained a few ROS-responsive Expressed sequence tag (EST) clones [10]. We also performed RNA-sequencing (RNA-Seq) to obtain a global transcriptome of the apical meristem, and to identify genes involved in the transformation from vegetative meristems to inflorescence meristems triggered by ROS and chilling [11].…”
Section: Introductionmentioning
confidence: 99%